Investigation on time management practices in measuringCalculus Test 1 performance of Applied Sciences students UiTM Tapah, Perak / Nor Faezah Mohamad Razi ... [et al.] - Mohamad Razi, Nor Faezah; Mohamad Ghadafy, Nurfarahin; Mohd Sukeri, Siti Arifah; Mohd Saupi, Muhd Luqman; Rupiwin, Munir Zaki; Ahmad, Siti Nurain Amanina (Universiti Teknologi MARA, Perak, 2019)
The aim was to determine whether Time Management Practices (TMP) affect the Calculus Test 1 Performance of Applied Sciences (AS) students of UiTM Tapah, Perak. Precisely, the objectives are to investigate the relationship between AS students' TMP for each component which are Time Planning (TP), Time Attitudes (TA), and Time Wasters (TW) with their performance, to investigate which item in the TMP affect the Calculus Test 1 Performance and to identify the actual factors in their bad time anagement. 154 students from Part 2 were selected as our sample by using cluster sampling technique. "Time Management Scale" was developed by Britton and Tesser (1991) were used as research instruments. By using Pearson correlation analysis, Time Planning (TP) is the only item that has a week positive linear correlation with their erformance. Descriptive analysis shows that last minute study is the actual factors of AS students' bad management of time.